MARGINALIZATION OF FEMALE CHARACTERS IN THE NOVEL "HATI SUHITA" BY KHILMA ANIS - Naida, Winka; Firmansyah, Muhammad Hilman; Akbar, Dioka Muhammad (Journal Civics And Social Studies, 2025)
This study is entitled "Marginalization of Women in the Novel 'Hati Suhita' by Khilma Anis". The formulation of the problem in this study is how is the form of marginalization of women in the novel "Hati Suhita" by Khilma Anis? This study aims to describe the form of marginalization of women in the novel "Hati Suhita" by Khilma Anis. This research is a qualitative descriptive study. The research methods that are relevant to this study are the description method and literature study. Data were collected through written documentation techniques. The research instrument used was a data card. The data were analyzed using descriptive analysis techniques. Descriptive analysis techniques are techniques that reveal characteristics by describing the form of marginalization of women in the novel being studied. The results of the study indicate that in the novel "Hati Suhita" there is a form of marginalization of women. Alina Suhita, the female character analyzed in this study, experienced marginalization. The marginalization action received by Alina Suhita began when she was asked to become the daughter-in-law of Kyai and Bu Nyai Hannan since MTs. The matchmaking was intended so that Alina would become the school leader in the Al-Anwar Islamic boarding school environment. Alina never had full power over herself, because since school everything had been prepared by Kyai and Bu Nyai Hannan. Likewise when Alina got married, she was marginalized because Gus Biru's feelings were still owned by his past, namely Ratna Rengganis.